Polyhedral Gauss sums, and polytopes with symmetry - Malikiosis, Romanos-Diogenes (2016)
We define certain natural finite sums of nn'th roots of unity, called GP(n)GP(n), that are associated to each convex integer polytope PP, and which generalize the classical 11-dimensional Gauss sum G(n)G(n) defined over Z/nZZ/nZ, to higher dimensional abelian groups and integer polytopes. We consider the finite Weyl group WW, generated by the reflections with respect to the coordinate hyperplanes, as well as all permutations of the coordinates; further, we let GG be the group generated by WW as well as all integer translations in ZdZd. We prove that if PP multi-tiles RdRd under the action of GG, then we have the closed form GP(n)=vol(P)G(n)dGP(n)=vol(P)G(n)d. Conversely, we also prove that if PP is a lattice tetrahedron in R3R3, of volume 1/61/6, such that GP(n)=vol(P)G(n)dGP(n)=vol(P)G(n)d, for n∈{1,2,3,4}n∈{1,2,3,4}, then there is an element gg in GG such that g(P)g(P) is the fundamental tetrahedron with vertices (0,0,0)(0,0,0), (1,0,0)(1,0,0), (1,1,0)(1,1,0), (1,1,1)(1,1,1).